2019
DOI: 10.1371/journal.pone.0209188
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prevalence and risk factors associated with Cryptosporidium infection in rural population of district Buner, Pakistan

Abstract: BackgroundCryptosporidium spp are important intestinal protozoan parasites that cause diarrhea in humans, domestic and wild animals. Its infection remains a main public health concern however, the epidemics in human being is still unclear, particularly in developing countries. There are several factors that may enhance the spreading of this parasite in human population especially in young children.MethodologyA questionnaire was designed to obtain the demographic and clinical data from the participants. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
41
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 53 publications
12
41
2
3
Order By: Relevance
“…These findings are consistent with the finding of Nishiura et al (2002) who found a high prevalence of Ascaris Lumbricoides in children of age group 5-8 years residing in the Northern areas of Pakistan [13]. Khan and collegues in 2019 reported 53% prevalence of Ascaris Lumbricoides in Pakistan and most of them were below the age of 15 years [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings are consistent with the finding of Nishiura et al (2002) who found a high prevalence of Ascaris Lumbricoides in children of age group 5-8 years residing in the Northern areas of Pakistan [13]. Khan and collegues in 2019 reported 53% prevalence of Ascaris Lumbricoides in Pakistan and most of them were below the age of 15 years [14].…”
Section: Discussionsupporting
confidence: 89%
“…More recently in a study by Khushdil et al (2016) cryptosporidiosis had a prevalence of 20.8% in children of Skardu [19]. In another study conducted in the district of Bunir, the prevalence of Cryptosporidium was 29.88% [14] and we found it to be 15.7%. A study by Mumtaz et al (2010) came up with the prevalence of Cryptosporidium with a value of 9.0%, being commonly observed in infants (<24 months) [20] but we observed a higher prevalence with broader distribution among all age groups.…”
Section: Discussionsupporting
confidence: 51%
“…Cryptosporidium oocysts were investigated in several studies either alone or along with other intestinal parasites among different population groups [13][14][15][16], as well as, in the environment [17][18][19] and domestic animals [20,21]. In Jordan, studies on Cryptosporidium were conducted on normal and immunocompromised patients among different age groups [10,12,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…oocysts excretion prevalence, OEP, або cases per se, CPS), а показник популяційної частоти специфічних Ig, який також називають індексом серопоширеності (ІСП), -відповідною верхньою межею поширеності криптоспоридіозу (англ. sero-prevalence index, SPI, або cases post-infection, CPI) [12][13][14][15][16][17].…”
Section: поширеність криптоспоридіозу у дітей з діареєю в донецькій оunclassified
“…Основні серед останніх -періодичність екскреції ооцист Cryptosporidium spp., що відображає особливість життєвого циклу цих найпростіших та змушує для їх виявлення збільшувати кратність повторюваного від-Оригінальні дослідження / Original Researches бору і дослідження ЗФ (при 3-разовому дослідженні через добу кожне наступне додає близько 20 % позитивних результатів від частоти отриманих у першому/одноразовому аналізі); домінування (> 60-80 %) субклінічних і легких швидкоплинних форм перебігу криптоспоридіозу із невисоким рівнем фекальної екскреції ооцист, які зазвичай залишаються недіагностованими; відносно низька чутливість мікроскопічного методу, що навіть за оптимальних умов його застосування дозволяє виявляти ооцисти паразитів у концентрації ≥ 10 4 у 1 г/мл досліджуваного зразка біоматеріалу; неможливість за допомогою мікроскопії надійно ідентифікувати види Cryptosporidium, у тому числі й найбільш клінічно значущі у патології людини C.parvum і C.hominis (спричинюють > 90 % випадків захворювань), які характеризуються ідентичною морфологією і тинкторіальними властивостями ооцист, подібною антигенною структурою, але не здатні обмінюватись генетичним матеріалом, певною мірою різняться за патогенезом і клінічним проявом обумовлених хвороб та епідеміологічними особливостями їх поширення[1,6,[23][24][25][26][27]. Тому саме показники частоти виявлення у досліджуваній популяції специфічних Ig, які в силу зазначених вище та низки інших обставин більш адекватно відображають інтенсивність епідемічного процесу криптоспоридіозу і відіграють провідну роль при оцінці соціально-медичної значимості цього паразитозу та при визначенні пріоритетних заходів для протидії його поширенню[12][13][14][15][16][17].Наскільки нам відомо, це перше дослідження серопоширеності криптоспоридіозу як серед населення в Україні взагалі, так і у когорті дітей з ГКІ зокрема. Із даних табл.…”
unclassified